The auditor's guide of 1869 : a review and computer enhancement of recently discovered old microfilm of America's first book on auditing by H. J. Mettenheimer /: a review and computer enhancement of recently discovered old microfilm of America's first book on auditing by H. J. Mettenheimer. (2020) - McMickle, Peter L; Jensen, Paul H
No abstract available